Effect of Doping and Excitation Wavelength on Charge Carrier Dynamics in Hematite by Time‐Resolved Microwave and Terahertz Photoconductivity. (20th May 2019) - Kay, Asaf; Fiegenbaum‐Raz, Mor; Müller, Sönke; Eichberger, Rainer; Dotan, Hen; van de Krol, Roel; Abdi, Fatwa F.; Rothschild, Avner; Friedrich, Dennis; Grave, Daniel A.
Abstract: The charge carrier dynamics of epitaxial hematite films is studied by time‐resolved microwave (TRMC) and time‐resolved terahertz conductivity (TRTC). After excitation with above bandgap illumination, the TRTC signal decays within 3 ps, consistent with previous reports of charge carrier localization times in hematite. The TRMC measurements probe charge carrier dynamics at longer timescales, exhibiting biexponential decay with characteristic time constants of ≈20–50 ns and 1–2 μs. From the change in photoconductance, the effective carrier mobility is extracted, defined as the product of the charge carrier mobility and photogeneration yield, of differently doped (undoped, Ti, Sn, Zn) hematite films for excitation wavelengths of 355 and 532 nm. It is shown that, unlike in conventional semiconductors, donor doping of hematite dramatically increases the effective mobility of the photogenerated carriers. Furthermore, it is shown that all hematite films possess higher effective mobility for 355 nm excitation than for 532 nm excitation, although the time dependence of the photoconductance decay, or charge carrier lifetime, remains the same. These results provide an explanation for the wavelength dependent photoelectrochemical behavior of hematite photoelectrodes and suggest that an increase in photogeneration yield or charge carrier mobility is responsible for the improved performance at higher excitation energies. Abstract : Time‐resolved terahertz microwave and terahertz spectroscopy are used to study the charge carrier dynamics of epitaxial hematite films. A physical basis for the wavelength dependent photoelectrochemical behavior of hematite is provided, demonstrating that an increase in photogeneration yield or charge carrier mobility is responsible for the improved performance at higher excitation energies.